Numerical Approach to Pile Load Test Using 3D Finite Element Method - Drusa, Marian; Vlcek, Jozef (Communications - Scientific letters of the University of Zilina, 2014)
Despite the various design approaches, the design of the pile foundations is still to be verified by the in-situ load tests to check the design stage assumptions. This paper presents the results of the study aimed at the soil properties and interaction between piles and soil. Calibration of the numerical model is based on the in-situ pile load test. It represents the case study, how variation of soil characteristics acting in interaction with pile and numerical technics can attain the coinciding results with tested outputs. Moreover, this study is contribution to the effort of designing the pile foundations more accurately with limiting occurrence of potential risks.